Peran Tutor dalam Meningkatkan Motivasi Belajar Peserta Didik Paket C Program Distance Learning di Homeschooling Kak Seto Surabaya - Eprilany Alifah Fil Husni; Sjafiatul Mardliyah (J+PLUS UNESA, 2023)
This study contains an analysis and description of the role of the tutor in carrying out his role in motivating the students of package c distance learning program at Homeschooling Kak Seto Surabaya. Homeschooling was originally an independent learning model supervised and guided by parents. Over time the home learning system or homeschooling was adapted to become an institution. This educational institution only focuses on carrying out a homeschooling learning system by increasing the learning methods used to adapt and help meet the needs of students. Currently tutors do not only play a role in teaching science, but tutors also play a role in providing motivation so that students can carry out the learning process in a conducive manner. This type of research approach uses descriptive qualitative methods. In this study, researchers gathered information from 11 research informants, who qualified to provide information to support research. The results of this study found that the tutor when carrying out his role in increasing the learning motivation of package c students was in accordance with the 10 indicators of the tutor's role. Then it was also found that in increasing students' learning motivation a conducive learning environment, the role of parents, and also a high interest in learning from these students were needed. In addition, when carrying out their role in increasing students' learning motivation, tutors find that they have several obstacles such as distance, and also learning environment conditions that are not conducive for students.